2021
DOI: 10.3390/curroncol28050313
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Advanced Epithelial Ovarian Cancer Associated with Cardiovascular Comorbidities and Type 2 Diabetes Mellitus

Abstract: Background: Ovarian carcinoma (OC) is usually diagnosed at an advanced stage, necessitating a multimodal approach that includes surgery and systemic therapy. The incidence of OC is approximately five times higher in women over 65 years of age. Cardiovascular comorbidities and type 2 diabetes mellitus, both prevalent at this age, can influence therapeutic strategy and have an adverse effect on survival. Objectives: Our study aimed to determine the impact of cardiovascular diseases and diabetes mellitus on survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…In addition, we found that diabetes was an independent risk factor for recurrence, especially for systemic recurrence. The similar results were previously reported in the epithelial ovarian cancer [ 10 , 17 ], pancreatic cancer [ 8 , 18 ], breast cancer [ 7 ], gallbladder cancer [ 9 ], colorectal cancer [ 13 , 19 , 20 ], and non-small-cell lung cancer [ 15 ]. However, the exact mechanism of how diabetes affects the prognosis of AC patients who underwent curative pancreaticoduodenectomy remains unclear.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, we found that diabetes was an independent risk factor for recurrence, especially for systemic recurrence. The similar results were previously reported in the epithelial ovarian cancer [ 10 , 17 ], pancreatic cancer [ 8 , 18 ], breast cancer [ 7 ], gallbladder cancer [ 9 ], colorectal cancer [ 13 , 19 , 20 ], and non-small-cell lung cancer [ 15 ]. However, the exact mechanism of how diabetes affects the prognosis of AC patients who underwent curative pancreaticoduodenectomy remains unclear.…”
Section: Discussionsupporting
confidence: 88%
“…Our data showed that comorbidities of higher ACE-27 score (moderate and severe) signi cantly increase the risk for adverse outcomes after cytoreductive surgery in elderly women with AEOC. Despite the existence of evidence demonstrating the relevance between comorbidity and survival in ovarian cancer [20], there were also studies in which no such difference was presented [8]. In the present study, overall survival of the severe ACE-27 grade was signi cantly worse than that of the none, mild, or moderate (p = 0.004).…”
Section: Discussioncontrasting
confidence: 79%
“…Due to the extra attention the cancer patients receive, the incidence of comorbidities may be higher than that in non-cancer patients [19]. Several studies have suggested an in uential role of comorbidities in process of ovarian cancer treatment [20,21], but more objective evaluation tools were seldom employed. Being different from the classical comorbidity assessment tool CCI, which simply sums up all items, ACE-27 classi es comorbidities based on their severity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies concerning the frailty index demonstrated that comorbidities as well as functional status, are associated with worse surgical outcomes and poorer OS [ 20 , 21 ]. An array of studies have suggested an influential role of comorbidities in the process of ovarian cancer treatment [ 22 , 23 ], though the incorporation more objective evaluative tools remains limited. In contrast to the classical comorbidity assessment tool CCI, which aggregates all items irrespective of severity, ACE-27 methodically categorizes comorbidities based on their severity.…”
Section: Discussionmentioning
confidence: 99%